An analysis of equivalence at word level in “The Lost Symbol” translation of English into Indonesian - Laila Sarah Puspita Sari (Jurnal Linguistik Terapan, 2013)
Based on finding the analysis there are eight types of problems found dealing with the equivalence at word level in The Lost Symbol translation of English into Bahasa: Culture-specific concepts, the source language concept is not lexicalized in the target language, the source-language word is semantically complex, the source and the target languages make different distinctions in meaning, the target language lacks of superordinate, the target language lacks of specific term, differences in physical or interpersonal perspective, difference in form, and the use of loan words in the source text. The most problem faced is the use of loan words, found five terms in English which are no equivalence word in Bahasa. The strategy used by the translator is to loan the word because the term is also familiar for the target reader.